The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/app9214562
|View full text |Cite
|
Sign up to set email alerts
|

Contaminants of Emerging Concern Removal by High-Energy Oxidation-Reduction Processes: State of the Art

Abstract: The presence of ‘emerging contaminants’, i.e., chemicals yet without a regulatory status and poorly understood impact on human health and environment, in wastewater and aquatic environments is widely reported. No established technology, to date, can simultaneously and completely remove all these contaminants, even though some Advanced Oxidation Processes (AOPs,) have demonstrated capacity for some degradation of these compounds. High-energy, radiolytic processing of water matrices using various sources: electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…Table 1. Comparison of standard potentials determined for some oxidants and radical species [47][48][49]. In the case of electrochemical degradation, it is important to select suitable electrode material, which should be not only stable enough during the process, but should also guarantee the formation of highly reactive radicals and oxidant species, resulting in high efficiency of pollutant treatment.…”
Section: P-type Semiconductor (Sc)mentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1. Comparison of standard potentials determined for some oxidants and radical species [47][48][49]. In the case of electrochemical degradation, it is important to select suitable electrode material, which should be not only stable enough during the process, but should also guarantee the formation of highly reactive radicals and oxidant species, resulting in high efficiency of pollutant treatment.…”
Section: P-type Semiconductor (Sc)mentioning
confidence: 99%
“…Among these factors, the costs of the process are very important. They include electrical energy consumption, which constitutes the main part of the operating costs [48,51]. PEC processes of wastewater treatment are regarded as consuming electrical energy and are usually characterized by the consumption of electrical energy per mass E EM (kWh/kg) or electrical energy per order E EO (kWh/m 3 /order), as described by the following equations [51,144]:…”
Section: Tio 2 Photoelectrodesmentioning
confidence: 99%
“…It has been shown that, in combination to conventional processes, they can achieve significant overall efficiency improvement not just towards removal of CECs but also of conventional contaminants [77]. Hence, Electron Beam and Plasma technologies could have a primary role in future strategies addressing emerging contaminants, contributing to optimized process energy demand [78].…”
Section: Towards More Energy-efficient Wwtpsmentioning
confidence: 99%
“…Martin-Pozo et al (2019) provided a review of the determination of CECs in wastewater sludge samples. Capodaglio (2019) discussed the state of the art of high-energy oxidation-reduction processes for water purification and wastewater treatment, which could play an important role in future strategies addressing CECs. Joseph et al (2019) reviewed the studies on the removal of various CECs with different physicochemical properties by various nanoadsorbents based on mental-organic framework (MOF-NAs) under different water quality conditions and discussed the recent literature on the synthesis and regeneration of MOF-NAs, and removal of CECs during water and wastewater treatment processes.…”
Section: Annual Literature Reviewmentioning
confidence: 99%